Numerical Modeling of RC Columns and a Modified Steel Model Proposal for Elements With Plain Bars - Melo, José; Varum, Humberto; Rossetto, Tiziana (Frontiers in Built Environment, 2020)
Cyclic load reversals (like those induced by earthquakes) result in accelerated bond degradation, leading to significant bar slippage. The bond-slip mechanism is reported to be one of the most common causes of damage and even collapse of existing RC structures subjected to earthquake loading. RC structures with plain reinforcing bars, designed and built prior to the enforcement of the modern seismic-oriented design philosophies, are particularly sensitive to bond degradation. However, currently perfect bond conditions are typically assumed in the numerical analysis of RC structures. This paper describes the numerical modelling of the cyclic response of two RC columns, one built with deformed bars and the other with plain bars, both with structural detailing similar to that typically adopted in pre-1970s structures. For each column, different software and modelling strategies to simulate the cyclic response were adopted. Numerical models were developed using the OpenSees and the SeismoStruct platforms and calibrated based on experimental tests results. Bond-slip effects were encompassed in the OpenSees models in a simple modelling strategy. A modified tri-linear steel material is proposed and adopted to consider the slippage of plain reinforcing bars by reducing the steel Young modulus. The parameters that define the tri-linear steel model were empirically obtained, based on the experimental results.